Individuals with and without military-related PTSD differ in subjective sleepiness and alertness but not objective sleepiness. (September 2021) - LaGoy, Alice D.; Sphar, Margaret; Connaboy, Christopher; Dretsch, Michael N.; Ferrarelli, Fabio; Laxminarayan, Srinivas; Ramakrishnan, Sridhar; Wang, Chao; Reifman, Jaques; Germain, Anne
Abstract: Posttraumatic stress disorder-related sleep disturbances may increase daytime sleepiness and compromise performance in individuals with posttraumatic stress disorder. We investigated nighttime sleep predictors of sleepiness in Veterans with and without posttraumatic stress disorder. Thirty-seven post-9/11 Veterans with posttraumatic stress disorder and 47 without posttraumatic stress disorder (Control) completed a 48-h lab stay. Nighttime quantitative EEG and sleep architecture parameters were collected with polysomnography. Data from daytime sleepiness batteries assessing subjective sleepiness (global vigor questionnaire), objective sleepiness (Multiple Sleep Latency Tests) and alertness (psychomotor vigilance task) were included in analyses. Independent samples t-tests and linear regressions were performed to identify group differences in sleepiness and nighttime sleep predictors of sleepiness in the overall sample and within each group. Participants with posttraumatic stress disorder had higher subjective sleepiness ( t  = 4.20; p  < .001) and lower alertness (psychomotor vigilance task reaction time ( t  = -3.70; p  < .001) and lapses: t  = -2.13; p  = .04) than the control group. Objective daytime sleepiness did not differ between groups ( t  = -0.79, p  = .43). In the whole sample, higher rapid eye movement delta power predicted lower alertness quantified by psychomotor vigilance task reaction time (β = 0.372, p  = .013) and lapses (β = 0.388, p  = .013). More fragmented sleep predicted higher objective sleepiness in the posttraumatic stress disorder group (β = −.467, p  = .005) but no other nighttime sleep measures influenced the relationship between group and sleepiness. Objective measures of sleep and sleepiness were not associated with the increased subjective sleepiness and reduced alertness of the posttraumatic stress disorder group.